Souvenir Product Design Based on Folk Art Identities for Travelers - Imsamraan, Suchart; Lerttevasiri, Pornthep; Phrompan, Intira (Asian Creative Architecture, Art and Design, 2021)
This research aims to study guidelines for designing souvenir products for tourists based on folk art identity. The sample groups included 22 domestic and foreign souvenir items manufactured between 2017 and 2020 based on their features. it must be a product that reminisces and creates memories about the local folk art identity of that location and reflected through design, with a particular identity serving as inspiration to stimulate tourist purchasing demand. To analyze the data from the example souvenir product, the researchers used Matrix Analysis table and Image Scale: Product positioning and summarized the results by using descriptive statistics such as frequency, mean, and percentage. According to the findings, souvenirs that use folk art identities as a source of design inspiration can be divided into three categories: 1) The “Conservative Group” is conservative in nature and has a complex character. 2) "Applied Group" has a modern aesthetic while retaining some of the complexity of folk art. 3) the “Modern Group” has a modern and simplistic look; it is divided into two subgroups: the luxury group, which uses a simplified style with less detail than the original. Then there is the cute, lively group. They’re brightly colored and come with play features. The six interconnected elements of tourist souvenirs product design and folk art identity are as follows: 1) Earthenware, wickerwork, carvings, leather work, cloth work, paper work, metal work, stucco work, painting, architecture, and writing are examples of folk art. 2) Legends, beliefs, cultures, and traditions are all reflected in local art. 3) Souvenirs Product’s features and consumer needs include interpretations, materials, sizes and function, and creative design. 4) Usable objects such as utensils, jewelry, toys, decorations, and foodstuffs are categorized by design category. 5) Product positioning: conservative or modern, complicated or simple. 6) Design for create a new and unique product by adapting, modifying, minifying, and combining.